Association of gestational hypertension with hypothyroidism in pregnancy - Mahemudmiya, Ranavadiya Mohammadfaizan; R., Sreekumari; Kartha, Niveditha; Serbin, Shalima; John, Bimal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: In recent years, the prevalence of hypothyroidism during pregnancy has been steadily increasing, a trend that is contributing to growing concerns about maternal and fetal health. Alongside the rising prevalence of hypothyroidism in pregnancy, gestational hypertension has emerged as an increasingly common and concerning complication. Methods: The primary objective was to study the association of gestational hypertension with hypothyroidism in pregnancy and secondary was to assess perinatal outcomes in pregnancies complicated by hypothyroidism. This was a case–control study conducted in 102 cases and 102 controls over a duration of one year in a multispecialty Credence hospital in a urban setting. Results: In our study, the distribution of age, parity, socioeconomic status, BMI, pre-existing complications- both medical and obstetric problems were comparable between groups . The odds of gestational hypertension were 2.15 times higher in cases compared to controls (OR: 2.15, 95% CI: 1.048–4.411) and this association was statistically significant (p=0.034). The incidence of preterm delivery was higher in hypothyroid women when compared to euthyroid women and was statistically significant OR=4.4 (95% CI: 1.203–16.096) (p=0.016). There was no statistically significant difference in the incidence of preeclampsia, FGR, anaemia, GDM, mode of delivery between the two study groups. Conclusions: The results of this study provided evidence for an association between hypothyroidism and the development of gestational hypertension offering an understanding of how thyroid dysfunction influences the course of pregnancy, which is consistent with previous studies. Early detection and management of hypothyroidism may help to reduce gestational hypertension and improve overall pregnancy outcomes.